Poesia e resistência: estilhaços de Chacal - Coimbra, Cláudia Cristina (2011)
This dissertation proposes to analyze Belvedere, poetic anthology of Chacal. The objectives are to show in the perspective taken by I lyrical, poetic aspects of resistance in the lyricism of Chacal, as well as reflect on the poetic devices of this resistance. To achieve these objectives, was selected the following issue: how the Chacal's poetry reveals production demonstrating the strength of his generation? How is the relationship between modernism of 22 and the so-called "marginal poetry" of the poetry of Chacal? For treatment of the problem, we select the hypoteses -as resistance poetry the poetic chacaliana reflect the angustias and the wishes of his generation; the poetic chacaliana, to engage in dialogue with the modernism of 22 objective, a relationship between literature and life and points to a lyric poetic. The theoretical foundation about the resistance relies on the conceptions of Alfredo Bosi, the critical concepts in, Antonio Candido, Heloísa Buarque de Hollanda and Hugo Friedrich. Among the conclusions, emerge: the poetry chacaliana acts as resistance to repressive society and homogenizing, acting as front this resistance can retrieve; the marks of modernism of 22 incorporate his poems dose of lyricism